2019
DOI: 10.1007/s11104-019-04050-9
|View full text |Cite
|
Sign up to set email alerts
|

Plant-soil feedback is shut down when nutrients come to town

Abstract: Background and aims The concept of plant-soil feedback is increasingly used to explain plant community assembly processes. Soil nutrient availability can be expected to play a critical role on these processes. However, little is known about the effects of nutrient availability on feedback direction and strength. Methods A plant-soil feedback experiment was performed with the grasses Anthoxanthum odoratum and Festuca rubra, and the forbs Leontodon hispidus and Plantago lanceolata, on soil with either low or hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 59 publications
(84 reference statements)
5
22
1
Order By: Relevance
“…Our findings are the first showing the importance of soil fertility on PSF in a tree species and are mostly consistent with the conceptual framework for PSF context dependence proposed by Smith-Ramesh and Reynolds (2017), and experimental work with herbaceous grassland species that shows stronger negative PSF in low fertility conditions (Petermann et al, 2008;in 't Zandt et al, 2019; but see Harrison and Bardgett, 2010 which found no effect of soil fertility on PSF). However, instead of the PSF becoming less negative (Petermann et al, 2008), absent (in 't Zandt et al, 2019, or weakly positive (Smith-Ramesh and Reynolds, 2017) we found PSF in higher fertility conditions to be equally strong, but in the opposite direction (i.e., seedling survival switching from worse to better in conspecific relative to heterospecific cultured soil).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings are the first showing the importance of soil fertility on PSF in a tree species and are mostly consistent with the conceptual framework for PSF context dependence proposed by Smith-Ramesh and Reynolds (2017), and experimental work with herbaceous grassland species that shows stronger negative PSF in low fertility conditions (Petermann et al, 2008;in 't Zandt et al, 2019; but see Harrison and Bardgett, 2010 which found no effect of soil fertility on PSF). However, instead of the PSF becoming less negative (Petermann et al, 2008), absent (in 't Zandt et al, 2019, or weakly positive (Smith-Ramesh and Reynolds, 2017) we found PSF in higher fertility conditions to be equally strong, but in the opposite direction (i.e., seedling survival switching from worse to better in conspecific relative to heterospecific cultured soil).…”
Section: Discussionsupporting
confidence: 89%
“…These soil biotic responses suggest increased negative PSF as soil fertility increases (as postulated by Revillini et al, 2016;Lekberg et al, 2018). However, in greenhouse experiments, fertilization reduced negative PSF (Petermann et al, 2008) or neutralized either positive or negative PSF (in 't Zandt et al, 2019). As outlined by Smith-Ramesh and Reynolds (2017), negative PSF may be expected to weaken due to a decline in nutrient stress and strengthened physical or chemical defenses (especially those that are N-based) against soil pathogens, and/or ability to re-grow lost tissue from non-structural carbohydrates.…”
Section: Introductionmentioning
confidence: 89%
“…We show that this relation was highly time-dependent, suggesting that species abundance fluctuations may underlie the contrasting results in literature. Our results add to an increasing number of theoretical (Broekman et al, 2019;Kandlikar et al, 2019) and empirical studies (in 't Zandt, Hoekstra, et al, 2020;in 't Zandt et al, 2019;Kulmatiski et al, 2017;Lekberg et al, 2018;Teste et al, 2017) emphasising that plant traits, competitive ability and soil nutrient availability must be taken into account in interpreting community effects of plant-soil feedback. Indeed, our cyclic patterns can only be understood if negative feedback is particularly prominent in more abundant species that profit more from readily available soil nutrients than less abundant species with positive feedback.…”
Section: Con Clus Ionsmentioning
confidence: 57%
“…Here, we investigated (a) if species relative abundance fluctuations over time resulted in fluctuations in the relation between abundance and single time point plant-soil feedback, (b) whether coupled species' increases and decreases in abundance in time were related to plant-soil feedback and (c) whether these abundance changes were moderated by manuring events. Apart from its direct effects on species relative abundances, nutrient enrichment has also been shown to modify or even overrule plant-soil feedback and its effect on plant species community composition (Castle et al, 2016;in 't Zandt, Hoekstra, et al, 2020;in 't Zandt et al, 2019;Manning et al, 2008). Based on our results, we discuss the long-term role of plant-soil feedback in shaping plant communities and the potential underlying mechanisms driving these processes.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation